Peningkatan Kemampuan Melakukan Operasi Hitung Dengan Menerapkan Model Penugasan pada Sekolah Dasar - MAILISNUR, MAILISNUR (Jurnal Daya Saing, 2017)
Abstract: Abstract: Methods of learning in mathematics becomes a unique challenge for math teachers in presenting the material to learners. Its success in providing the raw material effectively becomes a reference for learning. Through action research on class V subjects applied mathematics assignment models and analyzed descriptively. Based on the survey results revealed that the application of learning etode assignment in order to improve the results of student homework in class V in mathematics on the integer turns learning outcomes of students increased significantly. The data obtained show that after the implementation of the method of learning assignment, then proved their influence in a positive direction in improving the results of student homework in mathematics concerning arithmetic operations. Keywords: Keywords: Assignment Method, Learning Ability